(untitled) (Sains Humanika, 2016)
Nowadays, water pollution was viewed as a crucial issue and if not properly managed, it can threaten human health along with environment. Being so, various efforts have been taken by the government of Malaysia to ensure the Integrated Water Resource Management can be effectively implemented. In supporting the effective implementation of this approach, a Best Management Practices (BMPs) projects were carried out. Unfortunately, the implementation of these projects still remains in doubt and was unfamiliar by many parties. Therefore, this paper examined the outcome of BMPs Projects in the perspective of river water quality in Malaysia. By using content analysis technique towards 12 year period of data from the Malaysia Environmental Quality Report, starting from year 2002 to the year 2014, four projects were selected in order to identify is there any difference, especially on the river water quality status before and after BMPs Project have been carried out. The result of the studies revealed that, the BMPs projects have a potential in improving water quality status and there is a need to actively promote this project to the various stakeholders involved so that it can minimize Integrated Water Resource Management issues as well as enhancing the implementation.